2018
DOI: 10.1111/eva.12599
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide association analyses of fitness traits in captive‐reared Chinook salmon: Applications in evaluating conservation strategies

Abstract: A novel application of genomewide association analyses is to use trait‐associated loci to monitor the effects of conservation strategies on potentially adaptive genetic variation. Comparisons of fitness between captive‐ and wild‐origin individuals, for example, do not reveal how captive rearing affects genetic variation underlying fitness traits or which traits are most susceptible to domestication selection. Here, we used data collected across four generations to identify loci associated with six traits in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 102 publications
0
49
0
Order By: Relevance
“…This haplotype was also associated with the largest fish in Alaska and the Wenatchee River, suggesting a conserved genetic basis for older age at maturity among these haplotypes. Two previous studies of Chinook salmon failed to find a signal of age at maturity on the Ots17 (Micheletti and Narum 2018, Waters et al 2018). It is possible that these populations had little or no male-specific haplotype variation to detect; however, it is also possible that pooling samples by age class (e.g.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This haplotype was also associated with the largest fish in Alaska and the Wenatchee River, suggesting a conserved genetic basis for older age at maturity among these haplotypes. Two previous studies of Chinook salmon failed to find a signal of age at maturity on the Ots17 (Micheletti and Narum 2018, Waters et al 2018). It is possible that these populations had little or no male-specific haplotype variation to detect; however, it is also possible that pooling samples by age class (e.g.…”
Section: Discussionmentioning
confidence: 82%
“…In an aquacultural strain of Atlantic salmon, multiple genomic regions, including the VGLL3 gene, explained a total of 78% of the variation in age at maturity (Sinclair-Waters et al 2020). In Chinook salmon, the specific genes underlying variation in age at maturity are unknown but GWAS has identified SNPs associated with age at maturity on several autosomes (Micheletti and Narum 2018, Waters et al 2018) and male-specific sex chromosome haplotypes are associated with variation in size and age at maturity in male Chinook salmon from Alaska (McKinney et al 2019b). Despite the lack of specific knowledge of genes governing age at maturity in most salmon species, studies have consistently shown high heritability for this trait (Gall et al 1988, Heath et al 2002, Reed et al 2018) and QTL/GWAS studies have identified genomic regions associated with age at maturity in multiple species (Moghadam et al 2007, Haidle et al 2008, Ayllon et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no evidence that the Willamette Falls sample was from an admixed population, although the limited temporal variation in the samples precludes strong inferences about population structure, and mixed ancestry was possible (D. Van Doornik, personal communication). Future genetic research may resolve the origins of UWR Coho Salmon and spatial population genetic structure and could provide evidence for adaptive selection for specific genotypes (e.g., Anderson et al 2010;Waters et al 2018) or for the matching of genotypes to specific UWR tributary habitats.…”
Section: Future Research and Management Uncertaintiesmentioning
confidence: 99%
“…Few studies have investigated how artificial pellet feed might induce genetic changes in wild salmonid populations that are reared in captivity (Dender et al, 2018; Janisse et al, 2019), even though there is now an extensive literature on how captivity affects salmonid phenotypes, genetic characteristics and individual fitness (Le Cam et al, 2015; Christie et al, 2018; Waters et al, 2018; Fraser et al, 2019). In nature, early juvenile salmonids feed on drifting and benthic invertebrates, and the availability, type and nutrient composition of such prey will depend on habitat characteristics such as a flow rate and substrate (Braithwaite and Salvanes, 2005; Jonsson & Jonsson, 2011; Naslund & Johnsson, 2016).…”
Section: Introductionmentioning
confidence: 99%